INITIAL DEVELOPMENT OF TWO VARIETY LETTUCE IN FUNCTION OF TWO TYPES OF SUBSTRATES AND GROUND COVER - Souza, A. de A. L.; Moreira, F. J. C.; Araújo, B. de A.; Lopes, F. G. do N.; Da Silva, M. E. S.; Carvalho, B. da S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The aim of this study was to evaluate the initial development of two varieties of lettuce ’Ruby’ and ’butter’ depending on the types of substrates cultivation and the type of ground cover. The work was developed in agricultural greenhouse and Plant Health and Seed Laboratory at the Federal Institute of Education, Science and Technology of Ceará in Sobral. The seeds of two varieties were germinated in polystyrene trays of 128 cells; when they had four true leaves, about 20 days after sowing they were transplanted to the final spot in pots with 8.0 L capacity.The test was arranged in completely randomized design (CRD) factorial 2 x 2 x 3, split time, two varieties of lettuce ( ’Ruby’ and ’Manteiga’), two types of substrates (sand -SMO and manure -CMO), and three types of ground cover (control (no cover), carnaubastraw-CS and Mulching -MUL) in four evaluation times (10, 20, 30 and 40 DAT). According to the results obtained with the test, it was found that the use of different substrates do not interfere with the leaf area of lettuce varieties evaluated; The ground cover both mulching as carnauba straw, showed significant results for development of lettuce varieties used, showing that besides effective in retaining water in the soil, also helps to inhibitthe emergence of weeds, reducing thus the competition between them and lettuce varieties.